(3EQTGO GdQMef dCSHGH GdfRhd hGdfSN hGdJTGHg hJLhjO GdbQBfs - (3YWjI Gddg Hf YWjI GdHQgGfj GdTGaYj GdCLghQj,J (B1190 (3g` s ((3eMehO YHOGddWja GdWghjfi GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG jhGai fYeghHYO aEf Chdi eG jLH Gdhbha Ydjg s
(3BNQgG (B:s
(3hGdMeO ddg Ydi GdEJeGe hUdi Gddg hJe JHjVg ai jhe GdGKfjf s
(3HgG fXGe GdJYbjHIs
(3Ydjg hba ddCejQ CMeO CZG HGTG LGhjT (B1193s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B287s
Keywords: (3GdJaSjQ hYdhe GdbQBfs